KINERJA KEUANGAN PADA PT BANK NEGARA INDONESIA (PERSERO) DENGAN MENGGUNAKAN PBI NO.13/1/PBI/2011 - Kristianingsih – Politeknik Negeri Bandung (LPPM POLITEKNIK LP3I BANDUNG, 2017)
Each financial statements have a benefit for someone who’s use the financial statements, in the financial statements have a informations, and can be treated for some reason to used. Example for financial performance assessment, financial statements used for calculate from balance sheet, income statement, and cash flow statement. Financial performance assessment need some ratio, for example Quick Ratio, LDR, LAR, ROA, ROE, BOPO, NIM, CAR and DER. The data for this research is financial statements Bank Negara Indonesia period 2011-2015, who’s the biggest 4 bank and biggest assets in Indonesia. This research on Bank Negara Indonesia had composite rate 1 in all of ratio. Although for some ratio had composite rate 2, but doesn’t had effect for the conclusion this bank had a composite rate 1, it’s means Bank Negara Indonesia in Financial aspect had a very good value.